Genetic structure of Onchidium "struma" (Mollusca: Gastropoda: Eupulmonata) from the coastal area of China based on mtCO I. (3rd March 2016) - Zhou, Na; Shen, Heding; Chen, Cheng; Sun, Bianna; Zheng, Pei; Wang, Chengnuan
Abstract: The genetic diversity and population genetic structure of Onchidium "struma" were investigated using mitochondrial cytochrome c oxidase subunit I ( CO I) gene sequences. A total of 240 individuals representing 10 collection sites from across a large portion of its known range were included in the analysis. Overall, 42 haplotypes were defined and 97 polymorphic sites were observed. The O. "struma" populations had high haplotype diversity (0.9280) and nucleotide diversity (0.0404). We inferred that the early maturity and extensive survival habitat led to high genetic diversity of O. "struma" populations in China. Bayesian analysis and SAMOVA analysis showed significant genetic differentiation among populations and all populations were divided into two groups, (HK and HN) versus (GY, DF, CX, CN, ND and XM). The Mantel test revealed no significant correlation between geographic distance and genetic distance ( r  = 0.251; p  = 0.058). Restricted gene flow caused by a shorter term pelagic veliger stage and limited dispersal potential were inferred to result in genetic differentiation among populations based on nested analysis. HK population might be an invasive species by artificial transplantation.